ANALYSIS OF CYANIDE DISTRIBUTION IN GROUNDWATER NEAR PT. X GOLD MINING SITE - Leonardo Siregar, Ronald
Mining activities such as exploitation and extraction of minerals from mining will produce by product as tailing. One potential contaminants in tailings instead of heavy metal is cyanide. General treatment for tailings by mining industry (particularly underground mining) is backfilling. Backfilling is refilling the empty room that formed by previous mining activities with tailing materials. In other word, the tailing materials filled back to the cavity or empty room on the underground. Somehow tailings that used for backfilling exposed by water and dissolve the contaminant that consist in it such as cyanide, very possible it will be carried to the groundwater. Fate and transport contaminant in the groundwater and aquifer is difficult to control because it is not easy to determine the flow and stream boundary. The aims of this study is to determine how far fate and transport of cyanide in the groundwater at mining area. Method of this study is by doing analytical model Dominico based on . The software that used in this simulation is matlabs. Then, based on the simulations will perform prediction of how far fate and transport of cyanide in the next 50 years. The first step before all of the study is take sampel of tailing as contaminant sources that will be assumed as value of concentration C0. The laboratoium result of tailing sample show that the concentration of cyanide is 0.430 mg/L. The results of this simulations shows that cyanide is detected in the groundwater on the mining site.